Efficacy and safety of opioid-receptor antagonists for opioid-induced constipation: a systematic review and meta-analysis - Li, Yuanlin; Tu, Yuyuan; Zhou, Zihao; Liao, Defu; He, Ziyan; Li, Yan; Li, Boyu; Liu, Zhiren; Zhou, Zugang; Ai, Shuangchun (Frontiers in Pharmacology, 2026)
BackgroundOpioid-induced constipation (OIC) is a common and serious side effect of long-term opioid analgesic therapy. As traditional laxatives often show limited efficacy, it is crucial to explore treatment strategies that effectively relieve constipation without compromising analgesic effects. In response to this clinical need, Opioid-receptor antagonists have been approved for OIC. Although new evidence has emerged in recent years, a comprehensive analysis of efficacy outcomes (such as constipation symptoms, quality of life, and satisfaction) is still lacking.ObjectiveTo summarise and analyze evidence on the efficacy and safety of opioid-receptor antagonists in treating patients with OIC.MethodA systematic search of randomized controlled trials (RCTs) was conducted in PubMed, Embase, Web of Science, and the Cochrane Library up to 11 September 2025. A meta-analysis was carried out using RevMan and Stata, and the GRADE method was employed to evaluate the quality of evidence.ResultsA total of 20 studies (22 RCTs) involving 7,761 patients were included. Opioid-receptor antagonists significantly increased the change in spontaneous bowel movement (WMD = 1.10, 95% CI: 0.74–1.46); improved the proportion of responders (RR = 1.48, 95% CI: 1.28–1.70); enhanced quality of life (WMD = −0.20, 95% CI: −0.28 to −0.12) and treatment satisfaction (WMD = −0.32, 95% CI: −0.54 to −0.10). The patient assessment of constipation symptoms questionnaire showed a minor tendency of improvement (WMD = −0.16, 95% CI: −0.31 to 0.00). The incidence of serious adverse events indicates that no statistically significant difference was observed between treatment and placebo (RR = 0.88, 95% CI: 0.74–1.05). The incidence of other adverse events was higher in the treatment group than in the placebo group (RR = 1.22, 95% CI: 1.08–1.38).ConclusionOpioid-receptor antagonists are effective in treating patients with OIC. The risk of serious adverse events did not change statistically. The incidence of adverse events appears to increase with longer treatment duration, although this observation seems to require further validation.Systematic Review RegistrationCRD420251154280.